Preparation and electrochemical characterization of lithium cobalt oxide nanoparticles by modified sol-gel method - Khomane, Ramdas B.; Agrawal, Amit C.; Kulkarni, B. D.; Gopukumar, S.; Sivashanmugam, A. (Materials Research Bulletin, 2008)
Uniformly distributed nanoparticles of LiCoO2 have been synthesized through the simple sol-gel method in presence of neutral surfactant (Tween-80). The powders were characterized by X-ray diffractometry, transmission electron microscopy and electrochemical method including charge-discharge cycling performance. The powder calcined at a temperature of 900 degrees C for 5 h shows pure phase layered LiCoO2. The results show that the particle size is reduced in presence of surfactant as compared to normal sol-gel method. Also, the sample prepared in presence of surfactant and calcined at 900 degrees C for 5 h shows the highest initial discharge capacity (106 mAh g(-1)) with good cycling stability as compared to the sample prepared without surfactant which shows the specific discharge capacity of 50 mAh g(-1). (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Electrochemical properties; intercalation reactions; Layered compounds; Sol-gel chemistry; X-ray diffraction

Preparation of spherical particles of 1,1-diamino-2,2-dinitroethene (FOX-7) using a micellar nanoreactor - Mandal, Alok Kumar; Thanigaivelan, U.; Pandey, Raj Kishore; Asthana, Srinandan; Khomane, Ramdas B.; Kulkarni, Bhaskar Dattatraya (Organic Process Research & Development, 2012)
The need and preparation of spherical 1,1-diamino-2,2-dinitroethene (FOX-7) particles to meet certain special applications in high explosives and propellant formulation have been illustrated. Preparation of spherical FOX-7 particles by using a microemulsion technique has not been reported in the literature. In the present study, the preparation of spherical FOX-7 particles has been described using the novel concept of a micelle-based nanoreactor. Micelle-based nanoreactors have been prepared using a microemulsion of Triton X-100, cyclohexane, and water. Formation of spherical FOX-7 particles in the reverse micelle reactors have been described in the subsequent sections of this article. It is observed that spherical particles of FOX-7 are formed within 2 h in the microemulsion media. Analysis of the experimental results revealed that the particle size and shape of FOX-7 can be varied by changing the water/surfactant molar ratio in the microemulsion. Spherical particles synthesized by this method have diameters that are generally in the submicrometer to nanometer range. Impact sensitivity (h(50)) of the spherical particles obtained by the fall-hammer method is around 45 cm compared to regular synthesized FOX-7 (i.e., 50 +/- 5 cm) without any change in friction sensitivity, i.e. 36 kg. Loadability of the explosive charges can be enhanced by using these spherical particles of FOX-7.